Creating a conversational context through video blogging: A case study of Geriatric1927 - Harley, Dave; Fitzpatrick, Geraldine (Computers in human behavior, 2009)
Web-based communication technologies such as YouTube can provide opportunities for social contact, especially between older and younger people, and help address issues of social isolation. Currently our understanding of the dynamics of social interaction within this context (particularly for older people) is limited. Elaborating upon this understanding will make it possible to proactively facilitate and support this form of intergenerational social contact. This study focuses on the experiences of an 80-year-old video blogger (vlogger), Geriatric1927, and a video dialogue that develops between himself and three of his younger viewers on a particular topic. Through a multimodal interactional analysis, we show how vloggers create a conversational context between one another through the YouTube website. In particular we describe how vloggers use different communicative modes to establish eye contact, take turns in conversation, share embodied gestures, share their understandings and negotiate simultaneous audiences. Despite a disconnected and ambiguous sense of the other, YouTube is able to facilitate a conversational context in which common ground is shared and social contact and intergenerational communication can occur.